2019
DOI: 10.1080/08998280.2019.1664220
|View full text |Cite
|
Sign up to set email alerts
|

The ketogenic diet and the QT interval

Abstract: Long QT syndrome is a disorder of ventricular myocardial repolarization associated with an increased risk of life-threatening cardiac arrhythmias and sudden cardiac death. This report highlights a case of QT prolongation with torsades de pointes in a patient with baseline congenital long QT syndrome, believed to be precipitated by metabolic changes associated with the "ketogenic diet."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Moreover, epinephrine test is able to unmask the prolongation of the QT intervals in patients with ‘concealed LQTS’ [ 15 ]. The ECG may result normal at rest but based on the subtype, ECG abnormalities can be triggered by physical stress, emotional stress, dietary changes, certain drugs, or during sleep or at rest [ 16 , 17 ], and it has also been associated with metabolic syndromes and eating disorders [ 13 ]. LQTS primarily affects young people and is one of the main causes of SCD in this population [ 18 ].…”
Section: Brugada Syndrome and Long Qt Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, epinephrine test is able to unmask the prolongation of the QT intervals in patients with ‘concealed LQTS’ [ 15 ]. The ECG may result normal at rest but based on the subtype, ECG abnormalities can be triggered by physical stress, emotional stress, dietary changes, certain drugs, or during sleep or at rest [ 16 , 17 ], and it has also been associated with metabolic syndromes and eating disorders [ 13 ]. LQTS primarily affects young people and is one of the main causes of SCD in this population [ 18 ].…”
Section: Brugada Syndrome and Long Qt Syndromementioning
confidence: 99%
“…Selenium, ketone bodies, and alcohol levels were all within normal limits. One month later, she stopped the ketogenic diet, and the ICD showed no further arrhythmic episodes [ 17 ].…”
Section: Sudden Cardiac Death and Qt Prolongation Triggered By Ketogenic Dietmentioning
confidence: 99%
“…Later on, total cholesterol and triglyceride levels were found slightly elevated with a significant increase in low-density lipoprotein/high-density lipoprotein ratio than before [ 144 ]. Another study found sudden cardiac death of a patient on KD suffering from congenital long QT syndrome [ 145 ]. Few AEDs and magnesium deficiency also impair myocardial functioning by elongating QT interval.…”
Section: Safety Aspects Of Kd In Epilepsymentioning
confidence: 99%